The empty city - Hunter, Erin. (New York : Harper, 2012)
In the aftermath of the Big Growl that destroyed his city, a Lone Dog named Lucky must find a way to work with other dogs in order to survive in this frightening new world.
Kirkus Starred, May 2012.
Booklist, August 2012.
Voice of Youth Advocates (V.O.Y.A.), October 2012.
5.2
5-8
760L
Keywords: Dogs -- Juvenile fiction; Survival -- Juvenile fiction; Cities and towns -- Juvenile fiction; Dogs -- Fiction; Survival -- Fiction; Adventure and adventurers -- Fiction; Cities and towns -- Fiction; Fantasy; Dogs -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Adventure fiction; Fantasy fiction; Survival -- Fiction; Dystopias -- Fiction; Adventure fiction; Fantasy fiction